2020
DOI: 10.1016/j.jhepr.2020.100153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surgical approach and quality of resection on the probability of cure for early-stage HCC occurring in cirrhosis

Abstract: LLR vs. OLR 44 vs. 31% TO vs. No TO 33 vs. 18% Highlights Homogeneous population of 425 resected patients with early-stage HCC in cirrhosis. Textbook outcome following liver resection was achieved in 32.9% of patients. The minimal invasive approach increases the chance of achieving a textbook outcome. Textbook outcome following liver resection improves DFS and probability of cure. Minimal invasive treatments of early HCC have a promising curative effect. Lay summary The overall quality of surgical care, as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…9 Notably, the criteria of TO could be further adjusted to the aetiology of the malignancy. 10 Likewise, we acknowledge that the present benchmark values will require revision after further prospective and randomized LLR evaluation.…”
Section: To the Editormentioning
confidence: 90%
“…9 Notably, the criteria of TO could be further adjusted to the aetiology of the malignancy. 10 Likewise, we acknowledge that the present benchmark values will require revision after further prospective and randomized LLR evaluation.…”
Section: To the Editormentioning
confidence: 90%
“…Among hepatobiliary procedures, previous liver resection, ICC, gallbladder carcinoma, increasing tumour size (more than 3 cm), minor resection of posterior/superior segments, non-anatomical resection, (anatomical) major resection, biliary reconstruction, and major vascular invasion were all associated with decreased likelihood of achieving TO (OR 1 or less) 9 , 15 , 23 , 33 , 39 .…”
Section: Resultsmentioning
confidence: 97%
“…All studies found better TO rates in patients undergoing a laparoscopic procedure compared with an open procedure. Two of these studies included only patients with ICC 32 , 35 and three studies compared the laparoscopic and open approach in patients with HCC, portal hypertension and cirrhosis, and patients with any liver disease 9 , 31 , 33 . In both studies focusing on HCC, the laparoscopic approach proved to be a predictor of TO in multivariable analysis with Ors of 2.81 (95 per cent c.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies were excluded due to overlapping data, inclusion of patients without cirrhosis, unavailable statistical data, non-comparative studies, non-case matched studies (8,9,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Sixteen studies were eventually included (15)(16)(17)(18)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). The PRISMA flowchart of the literature review is presented in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%